Integration of Environmental Education Through the Practice of Painting with Natural Dyes at SMPN 21 Surabaya - Nusantara Prabasiwi; Tantra Sakre (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to describe and analyze the integration of environmental education through painting with natural dyes as a fine art learning strategy that shapes the ecological awareness of students at SMPN 21 Surabaya. A qualitative approach of the case study type to examine in depth the application of the integration of environmental education through painting with natural dyes at SMPN 21 Surabaya. Data was collected through observation, in-depth interviews, and documentation, with the main informants being art teachers, principals, and grade VIII students. Data analysis was conducted using the Miles and Huberman model, while research ethics were maintained through participant consent, confidentiality of identity, and respect for the learning process in schools. The results of the implementation of painting practice with natural dyes at SMPN 21 Surabaya show that this activity has succeeded in instilling the value of environmental concern in students. Students become more creative, reflective, and responsible in using natural resources wisely. There has been a change in positive attitudes, such as maintaining cleanliness, loving nature, and producing environmentally themed artworks. This practice can foster ecological awareness through contextual and fun art learning. Further research suggests that other schools adopt a similar model by adjusting to the local context and the availability of natural resources in the surrounding environment.